Glint removal assessment to estimate the remote sensing reflectance in inland waters withwidely differing optical Properties - Bernardo, Nariane [UNESP]; Alcântara, Enner [UNESP]; Watanabe, Fernanda [UNESP]; Rodrigues, Thanan; Carmo, Alisson [UNESP]; Gomes, Ana [UNESP]; Andrade, Caroline [UNESP] (My University, 2018)
The quality control of remote sensing reflectance (Rrs) is a challenging task in remote sensing applications, mainly in the retrieval of accurate in situ measurements carried out in optically complex aquatic systems. One of the main challenges is related to glint effect into the in situ measurements. Our study evaluates four different methods to reduce the glint effect from the Rrs spectra collected in cascade reservoirs with widely differing optical properties. The first (i) method adopts a constant coefficient for skylight correction (r) for any geometry viewing of in situ measurements and wind speed lower than 5 m·s-1; (ii) the second uses a look-up-table with variable ρ values accordingly to viewing geometry acquisition and wind speed; (iii) the third method is based on hyperspectral optimization to produce a spectral glint correction, and (iv) computes ρ as a function of wind speed. The glint effect corrected Rrs spectra were assessed using HydroLight simulations. The results showed that using the glint correction with spectral r achieved the lowest errors, however, in a Colored Dissolved Organic Matter (CDOM) dominated environment with no remarkable chlorophyll-a concentrations, the best method was the second. Besides, the results with spectral glint correction reduced almost 30% of errors.
Keywords: Inland waters; Optically complex systems; Remote sensing accuracy